The Concept of al-Ittihad: Abu Yazid al-Busthami's Thought and its Relevance in Sufism - Yogi Fery Hidayat (Yayasan Adra Karima Hubbi, 2024)
This research aims to examine the concept of al-Ittihad in the thought of Abu Yazid al-Busthami and its relevance within the tradition of Sufism, particularly in the context of Islamic spirituality. Al-Ittihad refers to the mystical union between human and God, where a Sufi feels a dissolution into the Divine during a profound spiritual experience. This concept is considered one of the central themes in Sufism but often sparks theological controversy among orthodox scholars, especially since it is perceived as violating the principle of tauhid (the oneness of God). Through shathiyat (mystical utterances) such as